Analysis the effect of job strain on nurses' quality of work-life: A mediating and moderating model - Sara Mohammadi; Belghis Bavarsad; Amin Hendighomashi (Wolters Kluwer Medknow Publications, 2022)
Background: One of the most important issues in all organizations is to improve performance of human resources to achieve goals. Therefore, it is necessary plans and solutions to reduce Job Strain (JS) and then increase Organizational Citizenship Behaviors (OCB), and Quality of Work-Life (QWL). The purpose of this study is to investigate the effect of JS on QWL with mediating role of OCB and moderator of employment status. Materials and Methods: This cross-sectional study was conducted on 300 nurses who were non-randomly voluntary selected among nurses working in seven educational hospitals in Ahvaz, Iran. Data were collected using demographic and occupational characteristics questionnaire and JS questionnaire with 12 items, OCB with 16 items & QWL with 26 items in the 5-point Likert scale. Data analysis was performed in SPSS22 using descriptive and inferential statistics, and structural equation modeling with SmartPLS3. Results: The results indicated the mean (SD) score of 49.56 (6.68) for JS (more than normal) and 58.84 (5.94) and 49.88 (7.69) for QWL and OCB, respectively. Spearman correlation coefficients show that JS has a negative relationship with QWL (r = -0.69, p < 0.001) and OCB (r = -0.54, p = 0.008). Also, nurses' employment status (Formal and Contractual) moderates the relationship between JS, QWL, and OCB. Conclusions: According to the results, job stress in nurses of Ahvaz hospitals was high and QWL was moderate (or less). Therefore, increased job stress leads to reduced QWL and OCBs of nurses. Also the employment Status and job security that it provides can modify this impact.